Measuring User Satisfaction with Stechoq Academy Platform Using End User Computing Satisfaction (EUCS) Method and Webqual 4.0 (Case Study: PT. Stechoq Robotika Indonesia): Pengukuran Kepuasan Pengguna Terhadap Platform Stechoq Academy Menggunakan Metode End User Computing Satisfaction (EUCS) dan Webqual 4.0 (Studi Kasus: PT. Stechoq Robotika Indonesia) - Paguini, Zuhra Reiqifakh; Sisephaputra, Bonda (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2024)
Stechoq Academy is a platform to provides e-learning facilities for students participating in the Certified Internship and Independent Study Program (MSIB). The aim of this research is to measure user satisfaction with the Stechoq Academy platform and to identify the factors influencing user satisfaction using the End User Computing Satisfaction (EUCS) and WebQual 4.0 methods, as well as aspects that require evaluation. The variables analyzed are the dependent variable is User Satisfaction, and the independent variables is Content, Accuracy, Format, Timeliness, Ease of Use, Usability, Information Quality, and Service Interaction. The data analysis method in this research uses the PLS-SEM approach with the SmartPLS application. The results of this study indicate that the average user satisfaction measurement for the Stechoq Academy platform is 3.14, categorized as Satisfied. Factors influencing user satisfaction with 8 hypotheses and 1 accepted hypothesis are the Content variable with a t-test value of 2.275 above 1.96 and a path coefficient value of 0.280 above 0.1, indicating a significant relationship and influence on user satisfaction with the Stechoq Academy platform.